Financial risk evaluation of listed companies in software and information technology service industry in China-Take M Company as an example - Cao, Shujie (International Journal of Global Economics and Management, 2024)
Software and information technology service industry are technology-intensive industries, and the great uncertainty of technological innovation, market investment and organization makes it possible for a large amount of capital invested by enterprises to suffer losses. Therefore, taking M company as an example, this paper uses TOPSIS method of multi-attribute decision-making to evaluate the financial risk of M company. The results show that the financial risk of M company tends to increase, among which profitability and development ability are the main factors affecting the financial risk. Software and information technology service enterprises must improve the level of financial risk prevention by improving the management level of accounts receivable, paying attention to cost control and enhancing the awareness of risk control.